Peripheral blood dendritic cells in children with acute Plasmodium falciparum malaria. - Urban, B; Mwangi, T; Ross, A; Kinyanjui, S; Mosobo, M; Kai, O; Lowe, B; Marsh, K; Roberts, D (2001)
The importance of dendritic cells (DCs) for the initiation and regulation of immune responses not only to foreign organisms but also to the self has raised considerable interest in the qualitative and quantitative analysis of these cells in various human diseases. Plasmodium falciparum malaria is characterized by the poor induction of long-lasting protective immune responses. This study, therefore, investigated the percentage of peripheral blood DCs as lineage marker-negative and HLA-DR(+) or CD83(+) cells in healthy children and in children suffering from acute malaria in Kilifi, Kenya. Comparable percentages of CD83(+) DCs were found in peripheral blood of healthy children and children with malaria. However, the percentage of HLA-DR(+) peripheral blood DCs was significantly reduced in children with malaria. The results suggest that a proportion of peripheral blood DCs may be functionally impaired due to the low expression of HLA-DR on their surface.